Exploring Teacher Assessment Conceptions in University EFL Writing Instruction - Qiang Guo (SAGE Open)
Teachers’ conceptions of assessment, as a dimension of assessment literacy, have an impact on their assessment practices. Chinese teachers of English as a foreign language (EFL) writing hold a range of conceptions of assessment because of the generally poor English writing proficiency of their students, the requirement in higher education for teachers to employ formative assessment, and the need to prepare their students to pass summative exams. In this study, teachers’ conceptions of assessment in Chinese university EFL writing instruction were examined. 406 university EFL teachers participated in a survey, with the focus on seven constructs. The results indicated that, overall, Chinese university EFL teachers held mixed yet compatible conceptions of assessment, without a clear predominance of either formative or summative orientation. Three distinctive conception profiles were identified. Of the background variables examined, only age was found to significantly influence teachers’ conceptions of assessment profiles. These findings have implications for the design of classroom assessment in higher education, teacher professional learning, and assessment reform policy.